KARAKTERISASI POTENSI PENGEMBANGAN KAWASAN CABAI DAN BAWANG MERAH DI KABUPATEN BIMA, NUSA TENGGARA BARAT - Popi Rejekiningrum; Sofyan Ritung (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The productivity of chili and shallot in Indonesia is still low, but Indonesia has great opportunities to increase chili and shallot productivity either through intensification and extensification. The objectives of the research are (1) to compile and develop land resources data, including climate and hydrology information in chili and shallot regions, (2) to compose maps of chili and shallot development regions. (3) to create recommendations on land, climate, and water management for chili and shallot development regions. Map of development of chili and shallot areas scale 1: 50,000 carried out by desk work and field verification. Recommendation of the development of chili and shallot commodity areas are arranged based on land suitability class by considering existing land use, and commodity centers on APL land (Other Use Areas). The results of the analysis show that Bima District has an area of 8,696 ha of shallot area and potential for extensification development of 60,363 ha, high development potential (P.1) covering an area of 4,675 ha and moderate (P.2) 55,688 ha. P.1 is quite suitable with the dominant nitrogen and phosphorus nutrient inhibiting factor, P.2 is marginal according to the dominant limiting factor of low rainfall. While for chili do not have an area because the existing land is scattered in a narrow area, but has a development potential of 46,159 ha consisting of high development potential (P.1) covering 3,280 ha, and moderate (P.2) covering 42,879 ha.